The Ayes Have It: The History of the Queensland Parliament 1957-89 - Wanna, John (ANU Press, 2010)
'The Ayes Have It' is a fascinating account of the Queensland Parliament during three decades of high-drama politics. It examines in detail the Queensland Parliament from the days of the 'Labor split' in the 1950s, through the conservative governments of Frank Nicklin, John Bjelke- Petersen and Mike Ahern, to the fall of the Nationals government led briefly by Russell Cooper in December 1989. The volume traces the rough and tumble of parliamentary politics in the frontier state. The authors focus on parliament as a political forum, on the representatives and personalities that made up the institution over this period, on the priorities and political agendas that were pursued, and the increasingly contentious practices used to control parliamentary proceedings. Throughout the entire history are woven other controversies that repeatedly recur - controversies over state economic development, the provision of government services, industrial disputation and government reactions, electoral zoning and disputes over malapportionment, the impost of taxation in the 'low tax state', encroachments on civil liberties and political protests, the perennial topic of censorship, as well as the emerging issues of integrity, concerns about conflicts of interest and the slide towards corruption. There are fights with the federal government - especially with the Whitlam government - and internal fights within the governing coalition which eventually leads to its collapse in 1983, after which the Nationals manage to govern alone for two very tumultuous terms. On the non-government side, the bitterness of the 1950s split was reflected in the early parliaments of this period, and while the Australian Labor Party eventually saw off its rivalrous off-shoot (the QLP-DLP) it then began to implode through waves of internal factional discord.